Imagery in the Geguritan Undhaling Rasa anthology by Siti Sundari: A Stylistic Study - Eleiana Elva Rafidah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Geguritan is a modern Javanese literary work in the form of writing resulting from the expression of the author's feelings. The object of this research is the Geguritan Anthology "Undhaling Rasa" by Siti Sundari. The purpose of this research is to describe the form of imagery in the Geguritan Anthology "Undhaling Rasa" by Siti Sundari. This research uses a descriptive qualitative method. The research focuses on imagery and is contained in four Geguritan entitled Cidra, Impening Wengi, Lamis, and Dalan Tembus. In this research, library techniques are used which are carried out by reading and recording the collected documents. Data analysis is carried out using the analysis model according to Miles and Huberman, namely: data reduction, data presentation, and drawing conclusions. Based on the analysis of the research results and discussion, it can be concluded that in the Geguritan Anthology "Undhaling Rasa" by Siti Sundari, imagery is obtained including: 1) Visual imagery, 2) Auditory imagery, 3) Olfactory imagery, 4) Tactile imagery, and 5) Motion imagery. In the Geguritan Anthology “Undhaling Rasa” by Siti Sundari, the dominant imagery is visual imagery and auditory imagery.